Tongue base exposure during TORS without the use of a mouth prop. Issue 4 (December 2016) - Miller, Matthew
Abstract This study describes a novel exposure technique for base of tongue trans-oral robotic surgery (BOT TORS) and early experience with it. The technique discussed involves placement of a suture through the mobile tongue with distraction and suspension of the tongue to the operating table. TORS is then performed per previously described techniques. In our series, 13 patients with either benign or malignant mass lesions involving the tongue base were treated with TORS at a tertiary academic medical center. We reviewed the rates of adequate exposure, console time, adequacy of resection (in malignant cases), complication rates, and costs associated with this technique. In our series, adequate exposure was achieved in 92.3 % of patients. Mean console time was 36 min. Negative surgical margins were achieved in all cancer resections. Five minor complications (tongue lacerations) were observed. Per-case cost attributable to this technique is $3.81. We conclude that BOT TORS is feasible without the use of a mouth prop. Operative times are consistent with those reported by centers that routinely use mouth props for BOT TORS. This technique does not appear to compromise margin adequacy during oncologic resections. Its use may result in a significant cost savings when compared to the FK and other similar retractors.